Gene drive-based population suppression in the malaria vector Anopheles stephensi - Xuejiao Xu; Jingheng Chen; You Wang; Yiran Liu; Yongjie Zhang; Jie Yang; Xiaozhen Yang; Bin Chen; Zhengbo He; Jackson Champer (Nature Communications)
Abstract Gene drives are alleles that can bias the inheritance of specific traits in target populations for the purpose of modification or suppression. Here, we construct a homing suppression drive in the major urban malaria vector Anopheles stephensi targeting the female-specific exon of doublesex, incorporating two gRNAs and a nanos-Cas9 to reduce functional resistance and improve female heterozygote fitness. Our results show that the drive was recessive sterile in both females and males, with various intersex phenotypes in drive homozygotes. Both male and female drive heterozygotes show only moderate drive conversion, indicating that the nanos promoter has lower activity in A. stephensi than in Anopheles gambiae. By amplicon sequencing, we detect a very low level of resistance allele formation. Combination of the homing suppression drive and a vasa-Cas9 line boosts the drive conversion rate of the homing drive to 100%, suggesting the use of similar systems for population suppression in a continuous release strategy with a lower release rate than SIT or fsRIDL techniques. This study contributes valuable insights to the development of more efficient and environmentally friendly pest control tools aimed at disrupting disease transmission.